The Potential Formation Of Embryogenic Callus Of The Hypoxia Condition Tolerant Of Soybean Varieties In Vitro - Sopa Putri Tanjung; Revandy I. M. Damanik; Luthfi Aziz Mahmud Siregar (Universitas Sumatera Utara, 2017)
The aims of the research was to determine the growth response and to identify the potential embriogenic callus of the hypoxia condition tolerant of soybean varieties in vitro. The research was conducted at the Plant Tissue Culture Laboratory and the Laboratory of Food Technology, Faculty of Agriculture, North Sumatera University, Medan, Indonesia, from March 2016 to September 2016. The result were analyzed with t-test with the combination between soybean varieties (Baluran, Gepak kuning, Willis) and the plant growth regulators (2,4-D, NAA, IAA) 10 mg/l. The parameters observed were: the percentage of plants forming callus, the callus colour, the callus texture, the callus histological, the fresh weight of callus, the total chlorophyll content, the protein concentration, the SOD activity and the POD activity. The result showed that the combination between varieties Gepak Kuning and Willlis with 10 mg/l 2,4-D significantly affected the growth of embriogenic callus, the fresh weight of callus, the total chlorophyll content, the protein concentration, the SOD and POD activities.